Facile Extraction of Cellulose Nanofibrils (Cnfs) from Wood Using Acidic Ionic Liquid-catalyzed Organosolv Pretreatment Followed by Ultrasonic Processing. Issue 13 (1st December 2022) - Zhao, Xin; Cheng, Fangchao; Hu, Yingcheng; Cheng, Ruixiang
ABSTRACT: Cellulose nanofibrils (CNFs) were successfully extracted from wood flour via atwo-step process involving acidic ionic liquid-catalyzed organosolv pretreatment and ultrasonic disintegration. Acomprehensive study was performed on the yield, morphology, crystallinity, chemical structure, and thermal stability of CNFs, as well as the mechanical properties and transparency of nanofilms. The results showed that 87.06% of the total lignin and 93.78% of hemicellulose were fractionated from lignocellulose after solvothermal pretreatment using 1, 4-butylene glycol. The isolated CNF maintained the type Icrystal lattice of native cellulose. Overall, the CNFs obtained after ultrasonication displayed asimilar morphology and crystallinity, but they had ahigher yield (41.82%), better thermal stability, and film-forming properties than those produced by concentrated acid hydrolysis. Solvothermal treatment using 1, 4-butylene glycol alcohol/water followed by ultrasonication is an ideal alternative CNF production method with alow environmental impact.